2022
DOI: 10.1021/jacs.2c08770
|View full text |Cite
|
Sign up to set email alerts
|

Low-Molecular Weight Small Molecules Can Potently Bind RNA and Affect Oncogenic Pathways in Cells

Abstract: RNA is challenging to target with bioactive small molecules, particularly those of low molecular weight that bind with sufficient affinity and specificity. In this report, we developed a platform to address this challenge, affording a novel bioactive interaction. An RNA-focused small-molecule fragment collection (n = 2500) was constructed by analyzing features in all publicly reported compounds that bind RNA, the largest collection of RNA-focused fragments to date. The RNA-binding landscape for each fragment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…The fragment also de-repressed a downstream target of miR-372, large tumor suppressor kinase 2 (LATS2) at the mRNA and protein levels while also reducing cell proliferation and invasion phenotypes associated with pre-miR-372-associated gastric cancer. 52 This study demonstrated that drug-like low molecular weight compounds can in fact be studied using 2DCS and that the method can detect high affinity binding interactions between fragments and RNA. Importantly, the fragment hit, 34, was bioactive in cells without any optimization.…”
Section: Two-dimensional Combinatorial Screening (2dcs)mentioning
confidence: 81%
See 2 more Smart Citations
“…The fragment also de-repressed a downstream target of miR-372, large tumor suppressor kinase 2 (LATS2) at the mRNA and protein levels while also reducing cell proliferation and invasion phenotypes associated with pre-miR-372-associated gastric cancer. 52 This study demonstrated that drug-like low molecular weight compounds can in fact be studied using 2DCS and that the method can detect high affinity binding interactions between fragments and RNA. Importantly, the fragment hit, 34, was bioactive in cells without any optimization.…”
Section: Two-dimensional Combinatorial Screening (2dcs)mentioning
confidence: 81%
“…That is, structural information about the fragments in complex with RNA informs optimization to improve affinity and selectivity of individual fragments and also informs how to link two or more fragments together. 42 Indeed, novel strategies to identify fragments that bind RNAs and the optimization thereof have been developed by various laboratories, employing NMR spectroscopy, [43][44][45] mass spectrometry, 45, dynamic combinatorial chemistry (DCC), 47 equilibrium dialysis, 48 labeled ligand displacement methods, chemical cross-linking and isolation by pull-down (Chem CLIP), 49,50 selective 2'-hydroxyl acylation analyzed by primer extension and mutational profiling (SHAPE-Map), 51,52 twodimensional combinatorial screening (2DCS), 52 and in silico methods. 42 Here, we describe the above-mentioned biophysical strategies employed to identify fragment binders, with one detailed example for each methodology.…”
Section: Fragment-based Approaches In Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…As proof of principle that it is indeed possible to define the molecular fingerprints of fragments and apply this information to target RNA selectively, a 2,500-member, RNA-focused fragment library (250 Da average molecular weight) was studied for binding to 3 × 3 and 3 × 2 internal loop libraries (ILLs) via 2DCS. 22 Three fragments selectively bound RNA structures that comprise the two RNA libraries, the affinity landscapes of which were defined. Interestingly, fragment 42 was predicted to bind the Dicer site of the miR-372 precursor (pre-miR-372) with the highest affinity based on HiT-StARTS statistical analysis (Figure 10C).…”
Section: Two-dimensional Combinatorial Screening (2dcs)mentioning
confidence: 99%
“…That is, structural information about the fragments in complex with RNA informs optimization to improve the affinity and selectivity of individual fragments and also informs how to link two or more fragments together . Indeed, novel strategies to identify fragments that bind RNAs and the optimization thereof have been developed by various laboratories, employing NMR spectroscopy, ,, mass spectrometry, , dynamic combinatorial chemistry (DCC), equilibrium dialysis, labeled ligand displacement methods, chemical cross-linking and isolation by pull-down (Chem CLIP), , selective 2′-hydroxyl acylation analyzed by primer extension and mutational profiling (SHAPE-MaP), , two-dimensional combinatorial screening (2DCS), and in silico methods . Here, we describe the above-mentioned biophysical strategies employed to identify fragment binders with one detailed example for each methodology.…”
Section: Introductionmentioning
confidence: 99%